ASIVA (AKU SIAP VAKSIN) AS AN EFFORT TO IMPROVE COMMUNITY KNOWLEDGE AND READINESS TO RECEIVE THE COVID-19 VACCINATION - Yurike Septianingrum; Lono Wijayanti; Sulistyorini Sulistyorini (Community Service Journal of Indonesia, 2021)
Information that is not true or commonly called a "hoax" about the Covid-19 vaccine circulating in the community makes people restless and confused, and if this is not addressed immediately, more and more people refuse to be vaccinated. Health cadres have a role in educating the public about Covid-19 vaccination, but in reality their activities have been inactive during the pandemic. The ability to conduct health education by utilizing technology is still lacking, so it is necessary to provide training on how to conduct health education to cadres. The purpose of this activity is to increase the knowledge and readiness of health cadres in an effort to increase knowledge and readiness of the community to receive the Covid-19 vaccination through the ASIVa (Aku Siap Vaksin) program. The method used in this community service activity is a participative educational approach, namely providing health education to cadres about the Covid-19 vaccine and training on how to use technology for health promotion. This activity was carried out for one month and was attended by ten health cadres. The results of community service show that the knowledge of the cadres is very good, skilled and interactive in carrying out health education.